(untitled) (Boletin Médico de Postgrado, 2020)
With the aim of describing the recurrences of papillary thyroid carcinoma in thyroidectomized patients treated at the Autonomous Oncology Service of Lara State, a cross-sectional descriptive retrospective study was conducted examining 140 medical records of patients with a diagnosis of papillary thyroid carcinoma registered during the period 2006-2017. Patients had an average age of 46.67 ± 13.94 years, being the most affected the 41-50 years and 51-60 years groups (26.43%, respectively); a predominance of females was observed (86.33%). The most performed surgical intervention was total thyroidectomy (44.29%) and total thyroidectomy with lymph node dissection (41.43%). Likewise, 35.71% received Iodine-131 as adjuvant treatment. The percentage of recurrences was 4.29%, being the most frequent local and regional with a prevalence of 33.33%, respectively; in addition, 66.67% of recurrences appeared during the first 5 years; 50% of these patients underwent total thyroidectomy and received Iodine-131. With these results, current information is provided in order to contribute to the preparation of surgical and oncological services for the care of cases of papillary thyroid carcinoma. It is important to maintain oncological follow-up in order to evaluate the evolution and prognosis of the different types of recurrences according to the place of appearance.